Blood glucose levels in healthy, term, appropriate for gestational age, exclusively breastfed infants - Lineus Hewis; Rulina Suradi; Taralan Tambunan (Indonesian Pediatric Society, 2005)
Objective This study aimed to determine blood glucose levels ofhealthy, term, appropriate for gestational age (AGA), exclusivelybreastfed infants at the age of 6, 12, 24, 48, and 72 hours of life,and to investigate the incidence of hypoglycemia in those infants.Methods All healthy, term, AGA infants born in CiptoMangunkusumo General Hospital, Jakarta, who were exclusivelybreastfed during the recruitment period of December 2003 untilFebruary 2004, were included in this study. These infants weresubjected to blood glucose level determination at the age of 6, 12,24, 48, or 72 hours of life, and the clinical signs of hypoglycemiawere monitored.Results Two hundred and fifteen blood samples taken from 137newborns were studied. There was no incidence of hypoglycemiaobserved, whether symptomatic or asymptomatic. The range ofblood glucose levels was between 41 mg/dl and 115 mg/dl. Themeans and the standard deviations (SD) of the blood glucose lev-els of the 6-, 12-, 24-, 48- and 72-hour old infants were 59.7 (11.98)mg/dl, 64.1 (13.51) mg/dl, 65.9 (14.42) mg/dl, 67.0 (14.95) mg/dl,and 78.6 (16.51) mg/dl, respectively.Conclusions The current concern for hypoglycemia in the popu-lation of healthy, term, AGA, exclusively breastfed infants duringthe first few days of life was not proven to exist. Therefore, there isno reason to resort to prelacteal feeding in such infants